Creative Writing Assistance to Support Poetry Reading-Writing Literacy Activities for Teacher’s at Ma'arif Educational Institutions Surabaya - Suharmono Kasiyun; Pance Mariati; Syamsul Ghufron (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
The low interest in reading and writing is a problem that needs to be addressed immediately, considering that reading and writing is an important means to absorb and develop knowledge, so that the Indonesian people become a quality society. The objectives of this Community Service are (1) to actively participate in improving students' competence in literacy at Ma'arif Surabaya Education in accordance with the literacy movement, (2) To increase children's literature mastery at Ma'arif Surabaya Educational Institutions (3 ) Improving students' poetry reading and writing skills (4) Supporting literacy activities of Ma'rif Surabaya Educational Institution students. The solution offered in this PKM is assistance in creative writing in supporting poetry reading and writing literacy activities.Participants consisted of 75 elementary school teachers. The training is carried out face-to-face, followed by online mentoring. The training material presented was poetry.After the poetry writing training is carried out, an evaluation will be held to identify the improvement in abilities and strengths and weaknesses as material for improvement in the next implementation. The results of the training showed that the teacher's poetry writing skills increased from being unable to compose poetry to being able to write. All the teachers who attended the training participated in the activity enthusiastically from start to finish. The material presented can be understood clearly and participants can apply it independently. This training activity has a good impact on improving the ability of teachers in literacy, especially in composing poetry. In the future, the poetry that has been created will be registered with Haki.